(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In this article, interesting methods for elementary class pupils to understand scientific concepts are carefully analyzed. Also, observation opportunities were used for students to understand scientific concepts. Each method is presented in detail in an interesting way.